Seaweed extract- based biostimulant as drought mitigation in sugarcane - Jacomassi, Lucas Moraes [UNESP] (2021)
Drought is one of abiotic factors most inherent to the decrease in field yields, inducing the plant to morphological and physiological responses, severely affecting plant metabolism due to cellular oxidative stress, even in C4 crops species as sugarcane. Algae extracts based as biostimulants are agricultural practices used to mitigate negative plant responses caused by drought conditions. However, it remain unexplored its effects as foliar aplication in sugarcane field exposed to water stress that can promote increases in plant metabolism, stalk and sugar yields, as well as an extracted juice with greater technological quality. Thus, study aimed to evaluate the effectiveness of using an algae extract based foliar fertilizer at application timings under the influence of the driest period of the year in late harvest sugarcane. The commercial sugarcane fields consisted of three experiments carried out in harvest seasons of 2018 (site 1), 2019 (site 2) and 2020 (site 3) in Brazil, using RB85-5536 and SP80-3280 varieties in different ratoons (5th and 3rd). The treatments consisted of application and no application timings of foliar biostimulant in June (sites 2 and 3) and July (site 1). The dose used was 500 ml a.i ha-1 in a 100 L ha-1 water volume. The use of seaweed extract (SWE) mitigated the negative effects of drought, increasing the stalk yield per hectare by up to 3.08 Mg ha-1, in addition to enabling greater accumulation of sucrose in the stalks by up to 2.8%, generating gains of 3.4 kg Mg -1 of sugar per hectare, which raises the quality of the industrializable raw material. The Trolox-equivalent antioxidant capacity of treated plants was improved by up to 22%, increasing the activity of antioxidant enzymes in relation to the decrease of the metabolite 3-carbon dialdehyde MDA. Leaf analysis shows an efficient metabolic activity for SWE aplication, decreasing carbohydrate reserve levels in leaves while increasing total sugars by up to 34%. By positively stabilizing the cellular redox balance of plants, the action of SWE increases biomass production, resulting in greater energy generation up to 10.5%. Thus, the SWE strategy is a tool in alleviating drought stress while enhancing sugarcane development, stalk yield and sugar production, and improving plant physiological and enzymatic processes.